PERBUATAN MALADMINISTRASI DALAM PEMBUATAN AKTA JUAL BELI OLEH PPAT DAN AKIBAT HUKUMNYA MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 2016 TENTANG PERATURAN JABATAN PPAT Jo. PERATURAN PEMERINTAH NOMOR 37 TAHUN 1998 TENTANG PERATURAN JABATAN PPAT (STUDI KASUS PUTUSAN PENGADILAN NEGERI JAKARTA SELATAN NOMOR: 129/Pdt.G/2016/PN.Jkt.Sel.) - Cecyllia Tamara B. Schouten; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2018)
The Land Deed Official (the PPAT) is a Public Official who is granted part of the authorities by the State in the implementation of land registration and the making of an authentic deed. The certificate must be made based on the deeds of the law by the parties. The deeds of the law based on Article 2 of the Government Regulation Number 37 of 1998, a sale and purchase, swap, gift, inbreng, granting right of building/right of use based on the land property rights, and granting of land mortgage. Based on the ordinance, the authentic deed can be used as evidence in case of dispute. In this case is usually a lot of the contempt of court. This act is called the Maladministration. Maladministration is poor management or regulation, especially in an offical capacity. Maladministration is bias, neglect, inattention, delay, incompetence, ineptitude, arbitrariness and so on and would be long and interesting list. Including abuse of power, unlawful procedures, unfairness and malfunction or incompetence. The author examines the problem using normative legal research methods supported by some interviews with some who are experts in the field of the land and maladministration. This act resulted in the existence of legal consequences. Due to the law could by law or may be cancelled. The sanctions awarded againts to the Land Deed Official who did this deed contained in Ministerial Decree of Agrarian Affairs and Spatial/Head of National Land Authority Number 112/Kep-4.1/iv/2017 Article 6 paragraph (1) include reprimand, warning, skorzing, onzetting even fired from The Land Deed Official membership.